Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Pakaian Pada Distro Bindos Store Ciseeng Bogor - Rangga Permana Putra; Abdul Khoir (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the effect of price and product quality on purchasing decisions at Distro Bindos Store Ciseeng Bogor, with a sample of 96 consumers. The method used is quantitative, with data analysis including classical assumption tests, simple and multiple linear regression, correlation coefficient, coefficient of determination, t test, and F test. The results showed that price has a significant effect on purchasing decisions with regression Y = 5.064 + 0.883 X1 and a correlation of 0.885. Product quality also has a significant effect with regression Y = 1.011 + 0.966 X2 and correlation 0.874. Simultaneously, price and product quality have a significant effect with regression Y = 1.094 + 0.510 X1 + 0.481 X2 and a coefficient of determination of 83.3%. Hypothesis testing shows that the value of t count> t table (18.420> 1.661) and (17.447> 1.661), and F count> F table (231.371> 3.09), which indicates a significant effect of price and product quality on purchasing decisions.